Mitophagy: An Emerging Role in Aging and Age-Associated Diseases - Chen, Guo; Kroemer, Guido; Kepp, Oliver (Frontiers in Cell and Developmental Biology, 2020)
Mitochondrial dysfunction constitutes one of the hallmarks of aging and is characterized by irregular mitochondrial morphology, insufficient ATP production, accumulation of mitochondrial DNA (mtDNA) mutations, increased production of mitochondrial reactive oxygen species (ROS) and the consequent oxidative damage to nucleic acids, proteins and lipids. Mitophagy, a mitochondrial quality control mechanism enabling the degradation of damaged and superfluous mitochondria, prevents such detrimental effects and reinstates cellular homeostasis in response to stress. To date, there is increasing evidence that mitophagy is significantly impaired in several human pathologies including aging and age-related diseases such as neurodegenerative disorders, cardiovascular pathologies and cancer. Therapeutic interventions aiming at the induction of mitophagy may have the potency to ameliorate these dysfunctions. In this review, we summarize recent findings on mechanisms controlling mitophagy and its role in aging and the development of human pathologies.